Bridge Collaborative Factsheet - Bridge Collaborative (Duke University, 2018)
The Bridge Collaborative is a global change agent driving a fundamental shift in how we think, plan, fund and work across sectors to make bigger change faster. We unite people and organizations with the shared evidence and tools to make a greater impact at the speed the world needs now.